I need help! I can’t afford it: the interplay of credit beliefs, anxiety, impulsive buying and risky indebtedness behavior in predicting Brazilians’ financial preparedness - Braga, Farah Diba M. A. Abrantes (2018)
The findings of this research bring out how relevant are personal factors (e.g., traits), buying, and financial behaviors in predicting individuals’ indebtedness and financial well-being, if compared to predictors of debt and determinants of credit limits commonly used in used in academia and the finance industry (e.g., income, debt/income ratio, past credit usage behavior, the number of credit cards, past debt behavior, gender, age, schooling, marital status). Consumer credit has undergone a tremendous increase during recent decades in both developed and emerging economies. Brazil, which has one of the highest consumer credit interest rates in the world, has also experienced a substantial credit expansion, providing credit access to consumers who had never had access to it before, notably those in the low-income group. Both previous experience and the literature associate the access to massive amounts of credit with suboptimal and destructive forms of behavior such as impulsive buying and over-indebtedness. This kind of behavior undermines the individual’s financial well-being. In the context of financial services and the emerging Brazilian economy, this research project proposes the concept of financial preparedness for emergency (FPE), defined as ‘an individual’s state of being financially prepared to cope with a financial shock. This research posits that FPE is a critical component of financial well-being and extending on previous literature framework of drivers and consequences of financial well-being, it proposes an integrative model that investigates the role of consumer credit, money attitudes, impulsive buying and indebtedness behavior, in predicting consumers’ financial preparedness for an emergency. Employing a covariance-based structural equation modeling (CB-SEM) method to test the proposed model empirically, this study finds that personal factors, buying, and financial behaviors play a key role as antecedents of individuals’ financial preparedness. The findings suggest that individuals who see their credit limits as part of their income or are anxious about money are more prone to engage in impulsive buying and risky indebtedness behavior. Consequently, by engaging in such patterns of behavior, individuals weaken their state to cope with financial shock, which in its turn might affect their financial well-being. This research further finds that the belief that credit limits serve as income does not change the risky indebtedness behavior of low-income consumers. Furthermore, the findings suggest that the number of credit cards, gender, schooling, and age does not play any role in financial preparedness nor any of the model’s relationships. An explanation of the outcomes and various of their implications is addressed in this study. Overall, the recommendations made focus on individuals, institutions, and policymakers and the responsibility of each of these players to adopt sustainable forms of behavior, such as, building credit usage awareness, adopting and regulating tools that better identify consumers’ traits and behaviors that might lead them, and eventually society as a whole, into sound financial well-being.